(3fHPI aj eYQaI CSGei GdWjhQ hGdMjhGfGJs - (3QVj GdOjf CHj HcQ Hf UGdM Hf GdNjGWs ((3RHjO s)
(3ChdgG (B:s
(3GdMeO ddg Ef GdSehQ hGdSfLGH hGdafc CfhGY KYGdH GdJQc s
(3BNQgG (B:s
(3GdbWfI bGd ai GdPNGFQ(B: (3SejJ HPdc dCfgG JbWf ai GdHjhJ GfJgi GdehLhO HNW SjOi GdSjO GdePchQ GfJgi eG hLO HNW s
(3Vef eLehY , JQJjHgG (B: (3ef U (B49 - (3U(B53s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdcdeGJ GdeaSQI HGdMeQI f Ydi GdfSNI JbjjOGJ cKjQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs